PENGEMBANGAN MEDIA BIG BOOK BERBASIS KEARIFAN LOKAL MELALUI METODE STRUKTURAL ANALITIK SINTETIK (SAS) UNTUK MENINGKATKAN MINAT DAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Ikromah, Nurul; Arbarini, Mintarsih; Tri Suminar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT This study is motivated by the lack of interest and ability of students' beginning reading and the use of media and methods that are not in accordance with the characteristics of first grade students, the lack of students' knowledge related to local wisdom and the lack of utilization of teaching materials in the teaching and learning process, so that it does not attract students' attention. This research aims to: 1) produce big book media based on local wisdom through the SAS method that is in accordance with the characteristics of grade 1 students; 2) produce big book media based on local wisdom that is suitable for grade 1 students who have been validated by media and material experts, student responses and teacher responses; and 3) produce big book media based on local wisdom that is effective for increasing students' interest and ability to read beginning. The development model used in this research is Research & Development (R&D) which adopts the ADDIE development model (Analyze, Design, Develop, Implementation, and Evaluation). The field trial subjects were 23 students of SD Negeri Banjaratma 04 as the control class, 26 students of SD Negeri Petunjungan 01 as the experimental class. The data collection techniques used included observation, interviews, questionnaires, and tests. The data that has been obtained is analyzed using independent t-test, paired t-test and N-Gain test. The results of this study showed 1) The results of the big book media feasibility test show that big book media is very feasible to use in learning with a percentage of media expert assessment of 90% and material expert validation obtained a percentage of 79% with very feasible criteria. The results of the teacher questionnaire obtained a percentage of 95% and a student response questionnaire of 98% with very feasible criteria. 2) Big book media based on local wisdom is effective to increase the interest and ability of first grade students. This is evidenced by the results of the significance value of the independent t-test and paired t-test, namely 0.000 and 0.000 <0.05. The N-Gain test results also showed a high increase in interest and ability in beginning reading. Keywords: big book media, local wisdom, SAS method, reading interest, beginning reading ability.